Sugar-sweetened beverages: taxation evidence from seven European countries and recommendations for implementation in other EU regions - Semerád, Pavel; Hospodková, Petra; Lamačová, Markéta; Rogalewicz, Vladimír; Babuněk, Ondřej; Dobranschi, Marian (Central European journal of public health, 2024)
OBJECTIVES: Higher-than-recommended sugar consumption (< 10% of total energy intake; WHO) leads to negative health impacts and the development of serious diseases. Sugar-sweetened beverages (SSBs) proved to be among the leading sources of free sugar intake, as they contain large amounts of added sugar. Our article aims to propose tax measures that will help change consumer behaviour and reduce SSBs consumption. METHODS: For a comparison of the forms of taxation, the experience of seven countries (Denmark, France, Hungary, Italy, Poland, Catalonia - Spain, and the UK) were analysed. The evolution of sugar consumption, consumption of sweetened drinks and obesity before and after the introduction and/or abolition of the sugar tax were reviewed. RESULTS: States that implemented a tax on SSBs were able to reduce SSBs consumption in the first year after the tax was introduced when states with a sugar-content-based tax have implemented it more effectively than states with a volume-based tax. Based on this finding, we propose basic design assumptions for the tax that can be used in European countries that have not yet introduced the tax. Progressive taxation divides beverages into 3 bands. The basic assumption is to encourage the desired consumer behaviour, i.e., consumption of SSBs with lower sugar content. The proposed tax design is applied to the conditions of the Czech Republic as a model case study. CONCLUSIONS: The results of our study suggest that SSBs taxation could be an effective policy intervention to improve population health by reducing the health impacts of SSBs among children and adolescents, although further studies are needed to prove the causality of the described associations.
Keywords: Taxes; Obesity; lidé; Europe; cukrem slazené nápoje; Evropa; Evropská unie; obezita; daně; Sugar-Sweetened Beverages; European Union; Humans